Morphology, Bedload, and Sorting Process Variability in Response to Lateral Confinement: Results From Physical Models of Gravel‐bed Rivers. Issue 12 (4th December 2020) - Carbonari, Costanza; Recking, Alain; Solari, Luca
Abstract : This paper uses flume experiments to investigate the influence of lateral width confinement on channel morphology, sediment sorting, and bedload transport. Three runs of about 60 hr were carried out under constant feeding rate equal to 0.6 l/s and 8 g/s, with a bimodal mixture of natural sediments, a fixed flume slope of 3%, and width imposed by lateral walls from 0.12 to 0.50 m in order to model three different flow confinement configurations. Despite the three runs transporting at the same rate on average, they presented different gravel‐bed river morphologies and different degrees of bed complexity. The three runs also presented differences in bedload transport rate fluctuations associated with different magnitude and mechanisms of bed storage and release of sediments. The intermediate width configuration (Run 2) was found to have a minimum storage and release of sediments compared with both the wider configuration (Run 1) and the narrower configuration (Run 3). Runs 1 and 3 were characterized by a significant storage and release of sediments resulting in a highly fluctuating bedload transport rate; however, while Run 1 (braiding morphology) stored and released sediments through lateral deposits and bed variations with planimetric sorting, Run 3 (single‐thread channel) stored and released sediments through variations in bed elevation accompanied by vertical sorting. We extrapolated this concept to the full set of gravel‐bed river morphologies, thus speculating about the channel morphology for optimal sediment transfer. Key Points: We perform flume experiments to represent poorly‐sorted gravel‐bed rivers with the same active channel width but different extents of lateral confinement Channel morphologies, geometries, sorting patterns, and bedload transport rates are strongly influenced by lateral width constraints Among the three configurations tested, the one with intermediate width confinement promotes a single‐thread to braided pattern and presents less variation in sediment transport rate